Diabolical Sedentarism in Post-Pandemic Education in the Southern Cone of Peru: The Fear of Returning to the Face-to-face (Innovaciones Educativas, 2024)
The return to presentiality has raised the alarms of the sedentary lifestyle that was built during the confinement and the tendency to the convenience of not leaving the nest. The manuscript explores the repercussions that the Covid-19 pandemic has had on educational institutions in Southern Peru. After a brief introduction, it addresses the face-to-face fear felt by the main actors in the educational corpus, also addressing the specific development of education in the Andes. As a ramification of the theoretical construct, students long for the winter past shaken by the vibrational waves of the Wuhan bat, because with the return to face-to-face, their comforts in the Internet network and the excuse of being in virtual classes to avoid taking care of certain academic and domestic responsibilities, will no longer be possible. As for the teachers' sphere, the frontal fight against the multiple educational problems in the country, abandoned for two long years, will be resumed. Finally, regarding the parents' stratum, a light of hope to see their children again wearing the sacred school uniform is starting to shine in a tunnel of worry.
Keywords: Distance Education; Atypical Student; academic teaching staff; Pandemic; School; Presentiality